An innovative hematopoietic stem cell gene therapy approach benefits CLN1 disease in the mouse model - Marco Peviani; Sabyasachi Das; Janki Patel; Odella Jno‐Charles; Rajesh Kumar; Ana Zguro; Tyler D Mathews; Paolo Cabras; Rita Milazzo; Eleonora Cavalca; Valentina Poletti; Alessandra Biffi (EMBO Molecular Medicine, 2023)
Abstract Hematopoietic stem and progenitor cells (HSPCs) can establish a long‐lasting microglia‐like progeny in the central nervous system of properly myeloablated hosts. We exploited this approach to treat the severe CLN1 neurodegenerative disorder, which is the most aggressive form of neuronal ceroid lipofuscinoses due to palmitoyl‐protein thioesterase‐1 (PPT1) deficiency. We here provide the first evidence that (i) transplantation of wild‐type HSPCs exerts partial but long‐lasting mitigation of CLN1 symptoms; (ii) transplantation of HSPCs over‐expressing hPPT1 by lentiviral gene transfer enhances the therapeutic benefit of HSPCs transplant, with first demonstration of such a dose–effect benefit for a purely neurodegenerative condition like CLN1 disease; (iii) transplantation of hPPT1 over‐expressing HSPCs by a novel intracerebroventricular (ICV) approach is sufficient to transiently ameliorate CLN1‐symptoms in the absence of hematopoietic tissue engraftment of the transduced cells; and (iv) combinatorial transplantation of transduced HSPCs intravenously and ICV results in a robust therapeutic benefit, particularly on symptomatic animals. Overall, these findings provide first evidence of efficacy and feasibility of this novel approach to treat CLN1 disease and possibly other neurodegenerative conditions, paving the way for its future clinical application.